Transport conductivity of graphene at RF and microwave frequencies. (19th February 2016) - Awan, S A; Lombardo, A; Colli, A; Privitera, G; Kulmala, T S; Kivioja, J M; Koshino, M; Ferrari, A C
Abstract: We measure graphene coplanar waveguides from direct current (DC) to a frequency f  = 13.5 GHz and show that the apparent resistance (in the presence of parasitic impedances) has an dependence (where ), but the intrinsic conductivity (without the influence of parasitic impedances) is frequency-independent. Consequently, in our devices the real part of the complex alternating current (AC) conductivity is the same as the DC value and the imaginary part is ∼0. The graphene channel is modeled as a parallel resistive–capacitive network with a frequency dependence identical to that of the Drude conductivity with momentum relaxation time ∼2.1 ps, highlighting the influence of AC electron transport on the electromagnetic properties of graphene. This can lead to optimized design of high-speed analog field-effect transistors, mixers, frequency doublers, low-noise amplifiers and radiation detectors.